1965
DOI: 10.1126/science.150.3705.1835
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit: Frequency of Suckling in the Pup

Abstract: Rabbit does were given free access to their young, access once a day, and access twice a day. In all three groups the young were nursed only once every 24 hours. Growth curves for the pups from day 2 of age to day 30 were identical for all three groups. The restriction of suckling to once a day appears to depend on the mother and not the pups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0
5

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(150 citation statements)
references
References 7 publications
1
144
0
5
Order By: Relevance
“…Comparison of the environmental conditions and the diet of wild rabbit and domestic rabbit kits during early development. [Zarrow et al (1965); Hudson and Distel (1982); Broekhuizen et al (1986);Gibb (1993); Hudson et al (1996a);Rödel (unpubl. ) A further possible reason for maladaptive behaviour in breeding does is that they are usually constantly exposed to acoustic and olfactory cues emitted by the kits when a permanently open nest box is used.…”
Section: Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the environmental conditions and the diet of wild rabbit and domestic rabbit kits during early development. [Zarrow et al (1965); Hudson and Distel (1982); Broekhuizen et al (1986);Gibb (1993); Hudson et al (1996a);Rödel (unpubl. ) A further possible reason for maladaptive behaviour in breeding does is that they are usually constantly exposed to acoustic and olfactory cues emitted by the kits when a permanently open nest box is used.…”
Section: Housingmentioning
confidence: 99%
“…Wild as well as domestic rabbits nurse their young once a day approximately every 24 h (Zarrow et al, 1965;Hudson and Distel, 1982;Broekhuizen et al, 1986;Hudson, 1995;Hudson et al, 1995Hudson et al, , 1996aHudson et al, , 1997, although the variation in nursing intervals appears to be larger in wild rabbits (Hoy, 2006;Rödel et al, 2012) than in domestic breeds under standardized conditions. In the domestic rabbit, it has been shown that milk yield decreases steeply during the late nursing period (Lincoln, 1974;Hudson et al, 1996a), and that increasing the number of potential nursing visits by does has no effect (Zarrow et al, 1965;Szendrő et al, 1993) or only a marginal impact (Seitz, 1997) on the pre-weaning growth and development of the kits.…”
Section: Dietmentioning
confidence: 99%
“…The survival of individual newborns depends then on their ability to orient to the mother's abdomen, to locate nipples and to suck efficiently in a highly constrained time span. Indeed, rabbit females nurse their litter once a day for less than 5 min (Zarrow et al, 1965;GonzalezMariscal, 2007). To locate the nipples rapidly, pups rely on odour cues emitted on the surface of the females' abdomen and/or in milk (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to several authors (Deutsch, 1957;Ross et al, 1963;Zarrow et al, 1965;Lincoln, 1974;González-Mariscal et al, 1994;Hudson et al, 1996;Hoy and Selzer, 2002;Selzer et al, 2004) nursing in rabbits is limited to a few minutes (2 to 5) once or twice a day. The doe enters the nest and positions herself over the litter, remaining almost motionless and not giving the kits any direct support to suckle.…”
Section: Discussionmentioning
confidence: 99%
“…Different opinions about nursing frequency of rabbit does are put forward in the literature. According to several authors (Venge, 1963;Zarrow et al, 1965;Hudson et al, 1996) rabbit does nurse their kits only once a day, whereas other authors state that, in cages as well as under semi-natural conditions, nursing events are observed more than once a day (Hoy, 2006). Maticz et al (2001) reported that 25% of the does nursed more than once a day and Selzer et al (2004) reports an average nursing frequency of 1.32 per 24 h in standard cages.…”
Section: Discussionmentioning
confidence: 99%